SULF2 overexpression positively regulates tumorigenicity of human prostate cancer cells - Vicente, Carolina M (J Exp Clin Cancer Res, 2015)
BACKGROUND: SULF2 is a 6-O-endosulfatase which removes 6-O sulfate residues from N-glucosamine present on heparan sulfate (HS). The sulfation pattern of HS influences signaling events mediated by heparan sulfate proteoglycans (HSPGs) located on cell surface, which are critical for the interactions with growth factors and their receptors. Alterations in SULF2 expression have been identified in the context of several cancer types but its function in cancer is still unclear where the precise molecular mechanism involved has not been fully deciphered. To further investigate SULF2 role in tumorigenesis, we overexpressed such gene in prostate cancer cell lines. METHODS: The normal prostate epithelial cell line RWPE-1 and the prostate cancer cells DU-145, and PC3 were transfected with SULF2-expressing plasmid pcDNA3.1/Myc-His(−)-Hsulf-2. Transfected cells were then submitted to viability, migration and colony formation assays. RESULTS: Transfection of DU-145 and PC3 prostate cancer cells with SULF2 resulted in increased viability, which did not occur with normal prostate cells. The effect was reverted by the knockdown of SULF2 using specific siRNAs. Furthermore, forced expression of SULF2 augmented cell migration and colony formation in both prostate cell lines. Detailed structural analysis of HS from cells overexpressing SULF2 showed a reduction of the trisulfated disaccharide UA(2S)-GlcNS(6S). There was an increase in epithelial-mesenchymal transition markers and an increase in WNT signaling pathway. CONCLUSIONS: These results indicate that SULF2 have a pro-tumorigenic effect in DU-145 and PC3 cancer cells, suggesting an important role of this enzyme in prostatic cancer metastasis.